Reviewing of Accuracy Assessment classification for Land use Map by Using Remote Sensing and GIS Techniques - Abdullah Abbas , Hamed; Sabah Jaber , Hussein (Journal of Planner and Development, 2026)
This paper presents a detailed overview of the historical development and current state of accuracy assessment in land cover mapping, specifically within the field of Remote Sensing of the Environment over the past two decades. It underscores the pivotal role accuracy assessment plays in refining land cover mapping techniques, stressing the significance of high-quality reference data, sampling methodologies, and accuracy metrics.Experience shows that urban expansion causes degradation of agricultural land, vegetation and water bodies. This urban sprawl contributes to many urban environmental problems such as poor air quality, rising temperatures and poor water quality.Accuracy assessment techniques have undergone enhancements to bolster their scientific robustness, resulting in a more stringent process. The collective body of research and practical applications has propelled accuracy assessment to a mature state.This research aims to use the best approach to estimate and evaluate the accuracy of land use map classification based on the use of high-resolution satellite images.Despite significant advancements, there remain avenues for improvement. This study identifies the necessity for improved documentation of accuracy assessment methodologies to bolster research endeavors. Moreover, as technological capabilities progress, new challenges emerge, such as the imperative to tackle the heightened capacity for extensive spatial and intensive temporal mapping of land cover. Addressing these challenges mandates the development of enhanced methodologies to effectively cope with them.Also, This paper focused on a literature review of satellite image classification techniques and their methods.We conclude from all this that the need to classify satellite images is essential to extract land use data to solve environmental problems and improve living conditions.